The two-tier board in Chinese A-share listed companies: its dynamics and functions - Zhou, Linyao (2023)
Two categories of the board mechanism are evident cross-nationally: the single-tier board (i.e., a board of directors) and the two-tier board. These two categories perform the essential board functions of monitoring and advising in different ways. Monitoring financial reporting quality and achieving better corporate performance are two key tasks for a company’s board. Previous literature on the single-tier board using agency theory and resource dependence theory suggested that board characteristics affect the two functions, proxied by earnings management and financial performance, in Western contexts. However, they do not provide the full story. Recent literature calls for multiple research designs that include qualitative methods, rather than examining only the “skeleton structure” in researching board mechanisms. The Chinese two-tier board is different from the European two-tier board, and very under- researched. The Chinese two-tier board simultaneously combines a supervisory board and a board of directors, but with the latter including independent directors (who are also an element of single-tier boards). Most previous Chinese studies, relying purely on agency theory, have quantitatively examined only the board of directors, and very few studies consider the effect of institutional environment on director behaviours and internal board dynamics. It is essential to investigate the characteristics and functionality of the two-tier board as a whole, including the supervisory board, being influenced by the Chinese institutional environment. The purpose of this research is to investigate the impacts and behaviours of two-tier boards in China. To investigate the characteristics and functionality of the two-tier board being influenced by the institutional environment, a mixed-methods approach (i.e., regression analysis and semi-structured interviews) is adopted. The quantitative method examines linkages between the two functions and their impacts, and the qualitative method investigates board dynamics and director behaviours. The research identifies three categories of two-tier board dynamics, especially the dynamics between supervisory and independent directors. This clarifies the two roles and provides a suggestion for their complementary potential in relation to the monitoring function. The research finds that two-tier boards, including supervisory boards, affect company financial performance and earnings management. Importantly, the institutional environment shapes board dynamics and director behaviour, and affects board functions. Chinese directors’ behaviour differs from the expected roles traditionally assigned to directors in European and other Western countries. This research makes significant contributions. It first contributes to agency theory, resource dependence theory and institutional theory. Although agency theory is dominant in corporate governance literature, its assumption regarding contractual relationships can be challenged in some emerging markets. Moreover, this research suggests that the director selection mechanism (i.e., the recommendation via relationship framework) is an additional approach for a company to obtain resources and reduce uncertainty. This study also extends comparative institutional literature. Although the two-tier board is affected by the regulative pillar, the behaviour logic is significantly affected by the normative and cultural-cognitive pillars. Additionally, this research adds to the literature, providing evidence on two-tier boards and internal board operations. More importantly, the current study is beneficial for both policymakers and listed companies. Concerning current developments in Chinese corporate governance, the research clarifies the role of the Communist Party of China (CPC) and provides evidence on the effectiveness of the Chinese approach.